Essentialist beliefs affect children's outgroup empathy, attitudes and prosocial behaviours in a setting of intergroup conflict. (10th May 2020) - O'Driscoll, Dean; Taylor, Laura K.; Dautel, Jocelyn B.
Abstract : Empathy for salient outgroups can promote positive intergroup attitudes and prosocial behaviours. Less is known about which factors may promote empathy, particularly among children, in contexts of intergroup conflict. Empathy may depend on underlying cognitions, such as social essentialist beliefs, that is, believing that certain social categories have an underlying essence that causes members to share observable and non‐observable properties. This study explored the influence of essentialist beliefs about ethno‐religious categories on outgroup‐directed empathy, attitudes and prosocial behaviours of children living in Northern Ireland ( N = 88; M = 7.09, SD = 1.47 years old). Bootstrapped chain mediation found that lower essentialist beliefs predicted greater outgroup‐directed empathy, which was positively related to outgroup attitudes, which in turn, predicted more outgroup prosocial behaviours. The findings highlight the importance of essentialist beliefs as an underlying factor promoting empathy, with links to prosocial behaviours in settings of intergroup conflict. The intervention implications are discussed.